HYDROTHERMAL DEPOSITION OF ZnO NANOSTRUCTURES ON SILICON WAFERS - E. B. Chubenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Results of hydrothermal deposition of undoped and Al doped ZnO nanocrystals on a single-crystal silicon wafers with a hydrogen passivated surface are presented. Hydrothermal deposition of undoped ZnO nanocrystals were carried-out in a equimolar solutions containing zinc nitride Zn(NO3)2 and hexamethylenetetramine C6H12N4. Aluminum nitride Al(NO3)3 were used as Al precursor during deposition of Al doped ZnO nanocrystals. The difference of the morphology of doped and undoped ZnO nanocrystals was shown. Photoluminescence properties of the doped and undoped ZnO nanocrystals were also studied.